Estudio de prefactibilidad para la instalación de una planta de producción de moringa oleifera en polvo enriquecida con camu camu para el mercado limeño - Angulo Acosta, Carlos Andrés (2018)
The principal objective of the project was to determine that a factory that produce powdered moringa oleifera enriched with camu camu is technologically, economically, financially, market and socially feasible. The results about a survey done around a specific population show up that 48,58% of the people are interested in consuming moringa oleifera, and natural markets (32%) and supermarkets (30%) are the principal places to buy natural products. In addition, the project demand for the year 2024 will be 415.135 units of terminated product. About the factory location, there were evaluated four regions: Lima, Lambayeque, Ica and Piura. The factors analyzed determine that Lima is the best region because of its proximity to the objective market. Specifically, the factory will be located in Puente Piedra, the city that has the best prices and citizen security. Additionally, the factory size was determined by the market with 415.135 annual units. 199.907 units need to be produced in a year in order to obtain earnings. By the year 2024, according to the production program calculated, there will be produced 1.573 units daily. The factory layout calculated was 1.065,88 m2 of total area (including the production area, administrative area, warehouses and maneuvering yard). The economically and financially evaluations of the project, determine that the total investment required is S/. 1’464.781,66. The most profitable option was incurring in a bank financing for 60% of the total investment, the IRR is more elevated and reached 62,38%. The VNA results in S/. 2’754.710,47 in 7 years, and the recovery period will be 2 years and 5 months, obtaining S/. 5,70 for each S/. 1 invested. Finally, the benefit generated is S/. 12’438.310,23 during the 7 years of the project. It proves that the project influences positively in the society.